Keep Love in Your Heart, Little One - Andreae, Giles 1966-; Vulliamy, Clara (Wilton, CT : Tiger Tales, 2007)
A parent shares words of love and encouragement as a child drifts off to sleep.
Originally published: London : Orchard Books, c2006.
Keywords: Love -- Fiction; Bedtime -- Fiction; Parent-child relationship -- Fiction; Stories in rhyme